Transactional Leadership and Its Impact on Reducing Administrative Truancy "A Field Study on Employees at the Education Monitoring Department in the City of Ajdabiya and Its Subordinate Offices" - Saad Ibrahim Issa (Journal of Scientific and Human Dimensions, 2026)
This study aimed to identify the impact of transactional leadership on reducing administrative truancy at the Education Monitoring Department in the city of Ajdabiya and its subordinate offices. The study population consisted of employees working at the Education Monitoring Department in Ajdabiya and its affiliated offices. The descriptive-analytical approach was adopted, and the data collection tool was a questionnaire. A total of 183 questionnaires were distributed, of which 179 were retrieved and valid for analysis, resulting in a loss of 4 questionnaires. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The most important findings of this study indicate a statistically significant inverse relationship between transactional leadership and administrative truancy in the education sector in Ajdabiya. Furthermore, the contingent reward dimension showed a significant inverse effect on administrative truancy, while the active management by exception dimension was found to be non-significant. In contrast, the passive management by exception dimension showed a direct positive effect on administrative truancy. The most important recommendations of this study include raising awareness among both employees and decision-makers in the Libyan Ministry of Education and its affiliated educational monitoring departments about the importance of adopting transactional leadership, restructuring the incentive, reward, and salary systems for educational monitoring departments in Libya, and directing educational monitors to adhere to official working hours while holding the negligent accountable and rewarding the diligent in order to eliminate truancy and improve the quality of the educational process.